Untersuchungen über die verwandtschaftlichen Beziehungen der Gattungen der bisherigen Glaphyrinae (Coleoptera: Lamellicornia). - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The taxonomic characters of the genera hitherto united under the subfamily Glaphyrinae are studied comparatively with the result that there are recognisable two lines of evolution with family rank, Lichniidae (= Lichniadae Erichson) and Glaphyridae Latreille. The family Glaphyridae may be divided into the subfamilies Glaphyrinae and Amphicominae. The two families form a separate line of evolution of hihger rank within the Laparosticti, characterized by the position of the two last abdominal stigmata.